Development of equivalent chain length (ECL) rules for lipid compounds - Vetter, Walter; Müller, Marco; Sommer, Katrin; Schröder, Markus; Hammann, Simon (Journal of Chromatography A, 2019)
Lipid compounds (fatty acids, tocochromanols, phytosterols) are difficult to separate by countercurrent chromatography (CCC) due to the existence of many similar structures and the limited availability of suitable biphasic solvent systems. Here we show that for these compound classes the success of a CCC separation can be directly derived from the chemical structures without the necessity of experimental determinations of K values. In most cases, lipid compounds differ in the total carbon number and the number of double bonds. For each structure the so-called equivalent chain length (ECL) can be calculated by subtracting a distinct value for each double bond from the total carbon number. Empirically, we verified that in the case of unbranched fatty acids (determined as methyl esters) one double bond corresponds with two carbons. Evaluation of CCC data from seventeen phytosterols in five plant oils and nine tocochromanol standards showed that one double bond was equal with one carbon for both lipid classes. Most compounds with different ECL can be separated by CCC but not those with the same ECL. In these cases, the selection of a suitable source for isolation of a particular lipid compound becomes very important. Knowledge of the impact of double bonds may also be a helpful tool for other substance classes.
Keywords: fatty acids; phytosterols; Countercurrent chromatography; equivalent chain length rule; tocochromanols